Does Formal Constraints Reduce CO2 Emissions? Indonesia’s Empirical Case - Darwanto, Darwanto; Santosa, Purbayu Budi; Handayani, Herniwati Retno; Aminata, Jaka; Arianti, Fitrie; Gozhali, Imam (International Journal of Energy Economics and Policy, 2019)
Rules (formal constraints) are expected to be able to shape human behavior to act based on what should and should not do accordingly. The connection of rules in the energy sector to carbon dioxide emissions depends on how far the rules are able to shape behavior as expected. The purpose of this study is to analyze the effect of rules (formal constraints) on CO2 emissions in Indonesia. Other variables used in this study are energy consumptions (fossil energy and renewable energy), and population growth which are in line with the previous study. The method used to help answer the research question is multiple linear regression analysis with ordinary least square approach. Using time series data in the period of 1990-2017 in Indonesia, this study found that fossil energy consumption and population growth have positive and significant impacts on CO2 emissions in Indonesia. Meanwhile, the consumption of renewable energy and the rules (formal constraints) have negative effects on the emissions of CO2 produced. These results show that rules (Formal Constraints) can indeed shape behavior, in this case the reduction of CO2 emissions. Keywords: formal constraints; CO2 emissions; energy consumption; energy policy; Indonesia JEL Classifications: O13, CO1, Q28 DOI: https://doi.org/10.32479/ijeep.8510